Probing the depths of evil and good : multireligious views and case studies - Gort, Jerald D.; Jansen, Henry; Vroom, H. M., 1945-2014. (Amsterdam ; New York : Rodopi, 2007)
In the few years since the attack on the World Trade Center on September 11, 2001, evil has become a central theme in the media and human consciousness: the evil of terrorism, the evil of secular culture, concern for poverty, and climate change ... Yet different cultures and religious traditions have different ideas of what evil is and what its root causes are. Although there is no massive clash of cultures, many disagreements and also conflicts in the world arise from the deep differences in views of evil. This volume explores religious views of evil. Scholars from different religions and fr.
The Descent into Hell and the Phenomenon of Exorcism in the Early ChurchGod's Good Plan and Evil Forces in This World; "Soul of a Woman Was Created Below"; Evil, Virtue, and Islamic Moral Theology; The Islamic Point of View on the Problem of Evil; Critical Humanism and the Problem of Evil; Evil from a Comparative Perspective; Index of Names; Index of Subjects; Contributors to this Volume.
Includes bibliographical references and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Ethics; Good and evil -- Religious aspects; Ethics; Morale; ethics (philosophy); PHILOSOPHY -- Social; PHILOSOPHY -- Ethics & Moral Philosophy; Ethics; Good and evil -- Religious aspects; Das Gute; Das Böse; Religion; Het Kwaad; Godsdiensten